Comparison of the Efficacies of Topical Liposomal Amphotericin B and Topical Clotrimazole in the Treatment of Pityriasis Versicolor - Ghahartars, Mehdi; Hosseini, Hossein; Khedri, Malek; Sadati, Maryam Sadat (Dermatology Practical & Conceptual, 2024)
Introduction: Pityriasis versicolor (PV) often exhibits recurrence even despite treatment, and a standardized therapy with a complete cure rate remains elusive. Given the fungicidal property of amphotericin B, its potential for PV treatment warrants investigation. Objectives: This study aimed to compare the efficacy of topical liposomal amphotericin B and clotrimazole cream in treating PV.Methods: A randomized controlled trial was conducted with 44 PV patients, aged 15 to 70 years, who were equally assigned to either the amphotericin or clotrimazole group. The trial was registered at the Iranian Registry of Clinical Trials on March 7th, 2022. PV diagnosis was confirmed in all patients through positive microscopic results. The amphotericin group received topical gel containing liposomal amphotericin B 0.4%, while the other group received topical cream containing clotrimazole 1%. Both treatments were applied twice daily to the affected skin lesions for 14 days. The primary outcomes assessed were mycologic cure, clinical cure, and complete cure at day 14 post-treatment.Results: Both drugs demonstrated successful treatment outcomes, with comparable rates of mycologic cure (77.3%), clinical cure (63.6%), and complete combined cure (63.6%). There was no significant difference between the groups in terms of the degree of cure (P=0.75). Adjustments for age, sex, lesion extent, and lesion site yielded insignificant risk ratio and risk difference estimates for the complete cure rate (P>0.05).Conclusions: The topical application of liposomal amphotericin B 0.4% is equally effective as topical clotrimazole 1% in treating pityriasis versicolor. These findings suggest that liposomal amphotericin B could be considered as a viable alternative treatment for PV. Further research is warranted to explore its long-term consequences and safety profile.